A Comparative Study Between Human Translation and Machine Translation as an Interdisciplinary Research - Hasibuan, Zainuddin (Institut Agama Islam Negeri Kudus, 2020)
Research purpose of the research is to determine the difference between human translation and machine translation. The data sources for this article come from several references, books, journals and articles related to the title of the discussion. Research findings of the research are that human translation is more effective and easier to understand when compared to machine translation which can only translate literal sentences or words without understanding the intent and purpose of the intended target language. So, machine translation language mainly focuses on the source language without paying attention to the target language. In terms of semantic meanings in machine translation, it is far away from the truth of the meaning it has when compared to the meaning of human translations. Therefore, machine translation can be said to be a literal translation that applies in general. So, the role of human translation is still bigger in the correct translation.